Radarbasierte Analyse der Hagelgefährdung in Deutschland - Puskeiler, Marc (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2013)
This study shows the development of an analysis of the hail hazard in Germany in high spatial resolution, based on radar- and lightning data.